Development and validation of the global diet quality score (GDQS) for children 24 to 59 months of age - Ali, Nazia Binte; Arsenault, Joanne E.; Castellanos-Gutiérrez, Analí; Moursi, Mourad; Deitchler, Megan; Batis, Carolina; Atayde, Agata Marina Perez; Kehoe, Sarah H.; Tadesse, Amare W.; Leonardo, Sofia; Nkengfack, Brunhilda Tegomoh; Diop, Loty; et al. (Oxford University Press, 2025)
Objectives To develop the Global Diet Quality Score (GDQS) for children aged 24-59 months and evaluate its performance in predicting outcomes related to nutrient adequacy and diet-related noncommunicable disease (NCD) risk.